Competition and Subsequent Risk-Taking Behaviour: Heterogeneity across Gender and Outcomes - Antonio Filippin; Francesca Gioia (Institute of Labor Economics (IZA), 2017)
This paper studies if competition affects subsequent risk-taking behaviour by means of a laboratory experiment that manipulates the degree of competitiveness of the environment under equivalent monetary incentives. We find that competition increases risk aversion, especially for males, but not in a significant manner. When conditioning on the outcome, we find that males become significantly more risk averse after losing the tournament than after randomly earning the same low payoff. In contrast, males do not become more risk-seeking after winning the tournament, while females' average risk-taking behaviour is unaffected by tournament participation and outcomes. We interpret our findings in terms of males' reaction to negative outcomes driven by intrinsic motives, such as emotions or a shift in the locus of control from internal to external.
Keywords: C81; C91; D81; 330; competition; risk attitudes; gender